EFEK MENONTON ACARA DI TELEVISI TERHADAP SOSIAL BUDAYA MASYARAKAT MUSLIM KOTA MEDAN - Fahrul Rizal (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2016)
The research titled “Efek menonton acara iklan dan sinetron  di televisi terhadap sosial budaya masyarakat muslim kota Medan”. The purpose of this research was to determine whether watching advertisements and Cintron on television give effect to the Muslim communities in Medan include worship, family, and society. To get the data, the location determined in the district of Medan Belawan, Medan Deli and Medan Petisah with a population of 225 598 with the sample 399 persons; then the data collected by using questionnaires. The data analyzed by using correlation Pearson and regression through SPSS. The result showed that watching advertisements and Cintron had very significant effect to social and culture of Muslim societies in Medan City.